Molecular characterisation, genetic variability and detection of a functional polymorphism influencing the promoter activity of OXT gene in goat and sheep. Issue 2 (14th March 2017) - Cosenza, Gianfranco; Iannaccone, Marco; Pico, Boipuso Alpheus; Gallo, Daniela; Capparelli, Rosanna; Pauciullo, Alfredo
Abstract : The purpose of the study described in this Research Communication was to report the full characterisation of the goat and sheep oxytocin-neurophysin I gene ( OXT ), their promoters and amino acid sequences. Using the genomic DNA as template, we sequenced and compared the whole OXT gene (3 exons), plus 958/960 nucleotides at the 5′ flanking region and 478/477 nucleotides at the 3′ flanking region, in 46 sheep and 24 goats belonging to different breeds/genetic types reared in Italy, Greece and Germany. The comparison of the obtained sequences showed a high degree of genetic variability at these loci . In particular, we focused on the SNP g.438T > C as possible example of trans-specific polymorphism. This SNP alters a putative binding site of the transcription factor Oct-1. The set-up of a luciferase assay confirmed that the C variant of this SNP negatively affects the promoter activity of the sheep OXT gene. The results of this study suggest that the SNP g.438T > C might be useful to promote association studies with traits/physiological processes controlled by this hormone.